(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the main criteria for distinguishing in the Ukrainian language participial formations and adjectives with the suffixes -уч- (-юч-), -ач- (-яч-), -ущ- (-ющ-), -ащ- (-ящ-) on the base of the works of eminent grammarians 20–30th of XX century. – H. Kurylo and O. Sinyavsky.